1994
DOI: 10.1073/pnas.91.6.2012
|View full text |Cite
|
Sign up to set email alerts
|

Neuroanatomical correlates of retrieval in episodic memory: auditory sentence recognition.

Abstract: This study used positron emission tomography (PET) to investigate the neuroanatomical correlates of remembering previously experienced events. Twelve young healthy adults listened to "old" meaningful sentences which they had studied 24 hr previously. As a control task the subjects listened to comparable "new" sentences that they had never heard before. Regional cerebral blood flow associated with each task was measured by PET scans using 150-labeled water.Cowparison (old-sentence task minus new-sentence task) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
196
2
3

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 416 publications
(227 citation statements)
references
References 22 publications
24
196
2
3
Order By: Relevance
“…Right prefrontal activation is observed during retrieval tasks in general (Tulving et al, 1994) and can be interpreted as reflecting strategic search or post-retrieval processes supported by material-independent manipulation of representations implemented by working memory (Wagner, 1999), as has been illustrated by neuroimaging studies of working memory (Petrides et al, 1993;McCarthy et al, 1994;Cohen et al, 1997;Courtney et al, 1997). Consistent with the right prefrontal activation, neuropsychological studies have demonstrated that the right, but to a lesser degree than the left, frontal damage impaired temporalorder retrieval performance when verbal materials were to be remembered (Milner 1971(Milner , 1991.…”
Section: Discussionmentioning
confidence: 74%
“…Right prefrontal activation is observed during retrieval tasks in general (Tulving et al, 1994) and can be interpreted as reflecting strategic search or post-retrieval processes supported by material-independent manipulation of representations implemented by working memory (Wagner, 1999), as has been illustrated by neuroimaging studies of working memory (Petrides et al, 1993;McCarthy et al, 1994;Cohen et al, 1997;Courtney et al, 1997). Consistent with the right prefrontal activation, neuropsychological studies have demonstrated that the right, but to a lesser degree than the left, frontal damage impaired temporalorder retrieval performance when verbal materials were to be remembered (Milner 1971(Milner , 1991.…”
Section: Discussionmentioning
confidence: 74%
“…Some evidence suggests that encoding (storage) and retrieval processes differentially engage the two sides of the brain. Several studies now suggest that the left prefrontal cortex is more involved with memory storage processes, and *' * ' that the right prefrontal cortex is more important for memory 6 0.7 0.8 retrieval (37,38). Consistent with this notion of asymmetrical lucose function, stimulation of the left AC alone is sufficient to modulate memory storage in rats (41), whereas the right AC in rats appears more involved than the left with memory retrieval (42).…”
Section: Discussionmentioning
confidence: 86%
“…Interestingly, bilateral activations within the ACC, the FP, and in the frontal operculum have been associated with the retrieval mode in which incoming sensory information is treated as a “retrieval cue” for information stored in episodic memory (Lepage, Ghaffar, Nyberg, & Tulving, 2000; Tulving & Schacter, 1990). The retrieval mode has been shown to become activated in old‐new recognition judgments on whether an item has been previously presented (Lepage et al., 2000; Tulving et al., 1994). Thus, in view of our results, retrieval mode‐type processing might contribute to the processing of distorted sentences by treating these as retrieval cues that are compared to memory representations created during the processing of the intact counterparts of these sentences.…”
Section: Discussionmentioning
confidence: 99%